2020
DOI: 10.1111/head.13939
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Impact of Parent Factors in Adolescents With Migraine and Tension‐Type Headache

Abstract: Objective To examine longitudinal associations between parent factors (parent headache frequency and disability, protective parenting behaviors, parent catastrophizing) with adolescent headache‐related disability and headache frequency over 6 months. Background Theoretical models propose bidirectional, longitudinal relationships between parent factors and adolescent headache. Few studies have examined this using prospective study designs. Design and Methods Participants were a cohort of 239 youth ages 11‐17 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…Only a few studies have addressed the long-term prognosis of childhood headache syndromes. Moreover, of these, most studies have focused on pediatric migraine [ 8 , 11 , 14 , 15 , 16 , 17 , 18 , 19 ], with very few evaluating TTH as well [ 7 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few studies have addressed the long-term prognosis of childhood headache syndromes. Moreover, of these, most studies have focused on pediatric migraine [ 8 , 11 , 14 , 15 , 16 , 17 , 18 , 19 ], with very few evaluating TTH as well [ 7 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some argue that migraine and episodic TTH in childhood are both part of the same headache syndrome or, more precisely, two ends of the same continuum [ 8 , 24 , 25 ]. This “continuum theory” of headache is also supported by those children and adolescents who present clinically with “mixed headache syndrome,” meaning a combination of TTH and migraine (mostly without aura).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that parents' physical and mental health is integrally related to the functioning of youth with chronic pain. [1][2][3][4][5] This study extends the literature by examining the potential intergenerational cascade from parent ACEs to parent physical and mental health to child pain in a clinical sample of youth with chronic pain. As expected, parent ACEs significantly predicted parent chronic pain status and depressive symptoms.…”
Section: Discussionmentioning
confidence: 74%
“…3 In this issue, we present the work that highlights the importance of the unique biopsychosocial factors that play a key role in the incidence and prognosis of pediatric headache disorders. From the importance of parental factors and early life stress in determining headache incidence and trajectories, [4][5][6] to considering the impact of societal policies on children and adolescents with headache disorders such as school start times, 7 we are starting to learn more about the biopsychosocial factors that are key to understand how pediatric headache disorders develop and how they are maintained.…”
mentioning
confidence: 99%